Asset Allocation of Czech Third Pillar Pension System compared to Finnish Autonomous Funds and long-term Effect on Investment Returns - Vandas, Martin; Musílek, Petr, 1965-; Derner, Tomáš; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2014)
The diploma thesis provides an analysis of Czech third pillar pension system asset allocation and resulting investment performance compared to pension system in Finland. The first part provides a detailed analysis of pension system in The Czech Republic and its key parameters with focus on investment regulatory limits, all in context of reform of the system effective as of 1st January 2013. The second part of this work provides comparable data and information of Finnish pension system and provides qualitative comparison of both pension systems. To support the qualitative analysis and first sight assessments, the third part of this work forms several statistical models evaluating investment performance of pension funds between years 2002-2012. An impact of individual asset groups to investment returns of both funds is evaluated for the same time period.
Vedoucí práce: Petr Musílek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor dipl. práce]; diplomové práce; master's theses